The sport student’s statistical literacy through statistical reasoning learning environment (SRLE) - N Hidayah; W Wahyudin; T Turmudi (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
The purpose of this research is to find the influence of Statistical Reasoning Learning Environment (SRLE) on the improvement of statistical literacy ability of sport students. This research is a quasi experimental research. The study was conducted in one of University in Bandung with 58 sport students as a sample. Sample consist of 29 students with direct learning and 29 students through SRLE learning. Data conducted by tes statistical literacy before and after learning approach applied by researcher. The results indicate that the enhanced statistical literacy abilities who obtain SRLE learning are better than students with direct learning. This means that learning with SRLE has a significant effect on improving students' statistical literacy abilities. It caused in SRLE learning, the student has opportunity to use that learning that make student more enthusiasm and easier to understand about concept statistics. Based on the result lecturerr can apply this approach in statistics learning to improve sport student’s statistical literacy ability.